Optimalisasi Layanan Dinas Kearsipan dan Perpustakaan Kota Mataram Sebagai Implementasi Public Relation - Ni Putu Mas Yudha Purwani; Rieka Yulita Widaswara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to understand how the Dinas Kearsipan dan Perpustakaan (DIARPUS) of Mataram City implements services as a form of public relations in attracting public interest to utilize the library. The study employs a descriptive qualitative approach with a case study method through direct observation and in-depth interviews. The findings indicate that DIARPUS provides various types of services as a public relations strategy, including circulation services, visitation services, e-book services, TP-BIS activities, literacy competitions, interlibrary cooperation, the Saturday–Sunday Reading Park, mobile library services, and the use of social media as a public communication channel. With these various facilities, DIARPUS prioritizes service optimization by providing a mini theater, comfortable reading spaces, and additional computers with adequate internet access. As a result, the services are able to increase public interest in the library and create a positive image that is friendly, safe, and relevant. Services serve as an implementation of public relations that require continuous optimization, and the results of the study show that improving service quality is a key strategy in building the image of the library institution in the eyes of the public.